Encountering Buddhism in Today's China: The Quest of Christian Cochini (The Macau Ricci Institute Journal, 2019)
AbstractChristian Cochini (1929-2018), the author of 50 Great Masters of Chinese Buddhism, was a man passionate about Chinese culture and Chinese religions, in particular. His love for China made him eager to foster intercultural and interreligious encounters. Before starting his Sinological studies he had specialised in the study of the Latin and Greek Fathers of the Church. His special attention paid to their monastic traditions, certainly prepared the way later on for his encounter with Chinese Buddhism. After several years teaching in China, Taiwan, and Japan, he moved to Hong Kong and Macao, where he embarked on a program of study and encounter with Chinese Buddhism that kept him busy till the end of his life. From around 2000 onwards Cochini became a pilgrim, travelling to every major Buddhist temple in China, and to many lesser-known centres. He recorded their cultural and scriptural riches, and engaged in long conversations with elder Masters whom he loved and revered. Deeply anchored in the Catholic and Jesuit tradition himself, he believed that interreligious dialogue was a privileged way to appreciate the spiritual traditions of the whole of humankind, in the hope of opening up the minds and souls of people from every nation and culture. Cochini was a visionary, and, for him, interreligious encounter was key to the betterment of humankind. Cochini published two voluminous books that are the fruit of hiscountless pilgrimages. The first one is about Buddhist temples in China. The second one – which is the one reviewed here – is about eminent Buddhist Masters.